Tunable Solvent Permeation Properties of Thin Film Nanocomposite Membrane by Constructing Dual-Pathways Using Cyclodextrins for Organic Solvent Nanofiltration - Heng, M.; Zhang, H.; Li, Y.; Xue, Y.; Pei, F.; Wang, J.; Liu, Jian (American Chemical Society, 2015)
© 2015 American Chemical Society. Design and fabrication of thin film nanocomposite (TFN) membranes with tunable solvent permeation properties is highly required to meet the demands of practical applications. Herein, a series of TFN membranes are elaborately fabricated by embedding cyclodextrins (CDs) into hydrophilic polymeric membrane (e.g., polyethylenimine, PEI). Within the active layer, hydrophobic cavities of CDs serve as exquisite pathways for nonpolar solvents, whereas the free volume cavities of the PEI matrix act as efficient pathways for polar solvents, constructing a dual-pathway nanostructure. The solvent permeation properties of these two pathways can be accurately tuned by adjusting the cavity size of CD and the fractional free volume (FFV) of PEI. Increasing the cavity size of CD allows larger nonpolar solvent to permeate, meanwhile increasing solvent flux. For instance, varying the cavity size from 0.60 to 0.75 nm elevates the toluene (0.60 nm) permeance from 0.13 to 2.52 L m-2 h-1 bar -1. Similar behaviors are observed for polar solvents when increasing the FFV of PEI by adjusting the PEI-CD interfacial interactions. Particularly, the isopropyl alcohol permeance is elevated from 3.37 to 4.16 L m-2 h-1 bar -1 when increasing FFV from 0.489% to 0.502%. Moreover, the rejection ability and extended trial of TFN membranes are also explored.